2012
DOI: 10.2528/pier11112110
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Imaging Approach for High Resolution Squinted Spotlight Sar Based on the Deramping-Based Technique and Azimuth NLCS Principle

Abstract: Abstract-The imaging problem of spotlight synthetic aperture radar (SAR) in the presence of azimuth spectrum folding phenomenon can be resolved by adopting the azimuth deramping-based technique and traditional stripmap SAR imaging algorithm, and this method is the so-called two-step processing approach. However, when the spotlight SAR operates on squinted mode, the echo two-dimensional (2D) spectrum is shifted and skewed due to the squint angle. In such case, the original two-step processing approach is not su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Finally, we compare the resonating modes between QOBR and QOBGR at SubMM-wavelengths. The Bessel-Gauss beam generated from the designed QOBGR have many promising applications in the MM-and SubMM-wavelength range, such as power transfer [26], millimeter wave imaging [27][28][29] and medium parameter measurement [30]. These applications are being studied at present.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we compare the resonating modes between QOBR and QOBGR at SubMM-wavelengths. The Bessel-Gauss beam generated from the designed QOBGR have many promising applications in the MM-and SubMM-wavelength range, such as power transfer [26], millimeter wave imaging [27][28][29] and medium parameter measurement [30]. These applications are being studied at present.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the spaceborne TOPS mode usually has a limited maximum azimuth beam steering capability, and existing stripmap focusing processors [16][17][18][19][20][21][22][23][24] can implement SAR data focusing well in this case. In addition to taking conventional stripmap imaging processors, problems of the aliased Doppler spectra and the azimuth output back folding in the SAR image should be resolved.…”
Section: Modified Ecs Algorithmmentioning
confidence: 99%
“…With the rapid development in the past years [1][2][3][4][5], the high-resolution SAR is capable of producing very high quality images. It is reported that typical sensor platforms is able to provide wide area search coverage (approximately 100 km 2 area per minute) at 1.0 m × 1.0 m resolution [6].…”
Section: Introductionmentioning
confidence: 99%